Early influence of auditory stimuli on upper-limb movements in young human infants: an overview - Ferronato, Priscilla A. M.; Domellöf, Erik; Rönnqvist, Louise (Frontiers in Psychology, 2014)
Given that the auditory system is rather well developed at the end of the third trimester of pregnancy, it is likely that couplings between acoustics and motor activity can be integrated as early as at the beginning of postnatal life. The aim of the present mini-review was to summarize and discuss studies on early auditory-motor integration, focusing particularly on upper-limb movements (one of the most crucial means to interact with the environment) in association with auditory stimuli, to develop further understanding of their significance with regard to early infant development. Many studies have investigated the relationship between various infant behaviors (e.g., sucking, visual fixation, head turning) and auditory stimuli, and established that human infants can be observed displaying couplings between action and environmental sensory stimulation already from just after birth, clearly indicating a propensity for intentional behavior. Surprisingly few studies, however, have investigated the associations between upper-limb movements and different auditory stimuli in newborns and young infants, infants born at risk for developmental disorders/delays in particular. Findings from studies of early auditory-motor interaction support that the developing integration of sensory and motor systems is a fundamental part of the process guiding the development of goal-directed action in infancy, of great importance for continued motor, perceptual, and cognitive development. At-risk infants (e.g., those born preterm) may display increasing central auditory processing disorders, negatively affecting early sensory-motor integration, and resulting in long-term consequences on gesturing, language development, and social communication. Consequently, there is a need for more studies on such implications.